The Building of a Symbolic Image - Randolph Langenbach (Oz, 2004)
Over the course of the last academic year, while on a Rome Prize Fellowship at the American Academy in Rome, Randolph Langenbach produced a 50-minute digital slide/video presentation called the Piranesi Project: A Statigraphy of Views of Rome. This video was inspired by the celebrated engravings that Giambattista Piranesi created between 1740 and 1778 of views of the ruins of ancient Rome, although it also includes the work of other artists.